HADITS ILMI: Diet Sebagai Upaya Penyembuhan - Masyhuri Rifai (IAI Al-Mawaddah Warrahmah Kolaka, 2018)
The subject of the study in this journal discusses how to cure and treat the times of the Prophet Muhammad. which in this case is contained in the hadiths, this is where we will be able to see whether the exact recipe of why the Apostles of his day looked healthy and rarely ill. The main object of this research is the hadith of the Prophet Muhammad. about the hadith narrated by Thurmuzi's priest. Regarding three types of contents from the stomach. The approach used is the language and socio-historical approach. Both of these approaches are used to examine the truth of the hadith and analyze the history of the hadith so that the meanings contained in each hadith of the Prophet are known. The results concluded that one proof of hadith: 1/3 for food, 1/3 for water, and 1/3 for air, in 2006, (1) Christian Leeuwenburgh of the Institute of Aging at the University of Florida found that reducing food portions was as much as 8% alone can prevent a lot of organ damage due to aging. (2) The discovery of Kalluri Suba Rao, a molecular biologist (2004), that eating less allows the body to more